Visual Analytics Tailored to Support E-Commerce Marketplace Advertising: The ECommVis Platform - Gino, Henrique Luiz Shibata (2025)
E-commerce platforms rely increasingly on digital advertising to drive merchant sales, yet existing analytics tools often fail to provide contextual insights that connect advertising performance with actionable business strategies. This is especially true in online marketplaces, where many sellers struggle to assess if their advertising performance from sponsored sales truly aligns with their selling strategy. Based on that, this study introduces ECommVis, a visual analytics system designed to address the gap between complex advertising metrics and merchant decision-making in e-commerce marketplaces. ECommVis integrates five complementary visualization components that provide temporal, spatial, and comparative perspectives on advertising performance: Orders Over Time (OS) tracks historical organic versus ad-driven sales through adjustable time frames; Geospatial Interactions (GS) visualizes spatial performance patterns using hexagonal grid mapping; Merchant Metrics (MC) displays advertising KPIs via interactive stacked charts correlating budget with engagement; Interactions by Weekday and Shift (HM) identifies optimal advertising windows across daily shifts and weekday patterns; and Time Period Comparison (TP) benchmarks campaigns across time frames using correlation, trend, and search term analyses. ECommViss usefulness and effectiveness is demonstrated through two usage scenarios developed with real food delivery platform data, and a user study with 11 platform experts.